2022
DOI: 10.1007/s00787-022-02014-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental sequelae of the COVID-19 pandemic in children with and without complex medical histories and their parents: well-being prior to the outbreak and at four time-points throughout 2020 and 2021

Abstract: The objective of this study is to understand the long-term mental sequelae for families over the course of the COVID-19 pandemic by longitudinally investigating the well-being of children with and without complex medical histories and their parents. Well-being of 200 children (between 7 and 18 years of age; 73 typically developing, 46 born very preterm, 73 with complex congenital heart disease) and 175 of their parents was assessed prior to and during the first (April–May 2020), second (October–November 2020),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 82 publications
2
7
0
2
Order By: Relevance
“…The inverse associations between pre-pandemic perceived social support and negative mental health symptoms during the early pandemic period in this sample of people who have injected drugs is consistent with research in non-PWUD samples ( Ehrler et al, 2022 , Herzog et al, 2022 , Hill et al, 2021 , Lee et al, 2020 ; C. H. Wang et al, 2021 ; Xu et al, 2020 ). We also observed a temporal association between pre-pandemic perceived social support and psychological resilience during the early pandemic period for which prior evidence has been limited.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The inverse associations between pre-pandemic perceived social support and negative mental health symptoms during the early pandemic period in this sample of people who have injected drugs is consistent with research in non-PWUD samples ( Ehrler et al, 2022 , Herzog et al, 2022 , Hill et al, 2021 , Lee et al, 2020 ; C. H. Wang et al, 2021 ; Xu et al, 2020 ). We also observed a temporal association between pre-pandemic perceived social support and psychological resilience during the early pandemic period for which prior evidence has been limited.…”
Section: Discussionsupporting
confidence: 85%
“…Many studies have demonstrated inverse associations between inter-pandemic perceived social support levels and various mental health symptoms during the pandemic ( Bik-Multanowska et al, 2022 , Iob et al, 2020 , McLean et al, 2022 , Rhubart and Kowalkowski, 2022 ). There is also some data demonstrating associations between greater perceived social support before the pandemic and a lower prevalence of mental health symptoms during the pandemic ( Ehrler et al, 2022 , Herzog et al, 2022 , Hill et al, 2021 , Lee et al, 2020 ; C. H. Wang et al, 2021 ; Xu et al, 2020 ). However, there remains limited data on the impact of pre- or inter-pandemic perceived social support on mental health following Big Events, including the COVID-19 pandemic, among PWUD.…”
Section: Introductionmentioning
confidence: 99%
“…Eine Studie mit Schweizer Kinder und Jugendlichen zwischen sieben und 18 Jahren [6] zeigt ein etwas anderes Bild als die österreichischen und deutschen Studien. Während das Wohlbefinden der Schweizer Kinder und Jugendlichen in der ersten Coronawelle im April/Mai 2020 beeinträchtigt war, erholte sich laut Schweizer Daten das Wohlbefinden der Kinder und Jugendlichen im weiteren Verlauf der Pandemie.…”
Section: Verschlechterung Der Psychischen Gesundheit In Zeiten Der Co...unclassified
“…Während das Wohlbefinden der Schweizer Kinder und Jugendlichen in der ersten Coronawelle im April/Mai 2020 beeinträchtigt war, erholte sich laut Schweizer Daten das Wohlbefinden der Kinder und Jugendlichen im weiteren Verlauf der Pandemie. Die Autor:innen führten die Ergebnisse darauf zurück, dass die Schulen in der Schweiz während der ers-ten Coronawelle geschlossen und alle Kinder und Jugendlichen im Homeschooling waren, während die Schweizer Schulen während aller folgenden Wellen offen blieben [6].…”
Section: Verschlechterung Der Psychischen Gesundheit In Zeiten Der Co...unclassified
“…An important risk factor for a deterioration was belonging to a vulnerable group, e.g. those with pre-existing trauma, pre-existing mental health problems, lower socioeconomic status or financial difficulties, poor family functioning or low social support [ 3 , 4 , 10 ]. More exciting, some individuals seemed to show resilience to or even benefit from the pandemic if they reported reduced bullying, more sleep, and/or more exercise [ 7 ].…”
mentioning
confidence: 99%